Questions Of Deviant Behavior, Prepathological And Pathological Mental Disorders The Practical Psychologist Specialized School – Secondary School - Prostomolotov, V. F.; Seredniak, Zh. M. (Psychiatry, Neurology and Medical Psychology, 2016)
Article was writen on the materials the school psychologist about a study aimed at identifying the factors that influence the occurrence prepathological and pathological mental disorders that contribute to the formation of deviant behavior among students of junior and middle classes. The article deals with questions of pedagogical, psychological and social factors of pathogenetic orientation which will develop an appropriate system of corrective measures aimed at reducing the development of the students’ deviant behavior.